KAPABILITAS KEWIRAUSAHAAN DAN KEMAMPUAN DINAMIS PERUSAHAAN: PERAN MEDIASI DARI PEMBELAJARAN ORGANISASIONAL - Maria Pampa Kumalaningrum; Rahmat Purbandono (Jurnal Riset Manajemen dan Bisnis, 2014)
Dynamic capabilities are regarded as a strategic premise to creating, maintaining and upgrading sustainable competitiveness. Considering organizational learning as a mediator variable, this study tests the relationship between entrepreneurial capabilities and dynamic capabilities. More specifically, the factor analysis method was employed to verify that dynamic capabilities are comprised of four dimensions, i.e. environmental sensing capabilities, change and renewal capabilities, technological and organizational flexibility capabilities. The research used UMKM in Yogyakarta and Solo as research sample. It was found that entrepreneurial capabilities has a significantly positive effect on dynamic capabilities, while organizational learning, which has significantly positive effect on dynamic capabilities, plays a partial mediating role between the two. These findings indicate that companies can build dynamic capabilities through different levels of organizational learning in the context of innovative and proactive atmosphere. Keywords: Entrepreneurial Capabilities, Organizational Learning, Dynamic Capabilities,